2019
DOI: 10.1029/2019ja026475
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Similarity of ICME Flux Ropes: Observations by Radially Aligned Spacecraft in the Inner Heliosphere

Abstract: Interplanetary coronal mass ejections (ICMEs) are a significant feature of the heliospheric environment and the primary cause of adverse space weather at the Earth. ICME propagation and the evolution of ICME magnetic field structure during propagation are still not fully understood. We analyze the magnetic field structures of 18 ICME magnetic flux ropes observed by radially aligned spacecraft in the inner heliosphere. Similarity in the underlying flux rope structures is determined through the application of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 124 publications
13
101
1
Order By: Relevance
“…It is important to note that our findings (scaling of the peak magnetic field strength in the ejecta with heliocentric distance) are in good agreement with previous statistical studies. In a study published after the initial submission of this manuscript, Good et al (2019) performed a static Lundquist flux rope fitting (Burlaga, 1988;Lepping et al, 1990) for 18 interplanetary flux ropes observed in conjunction between radially aligned spacecraft in the inner heliosphere. Applying the same fitting technique for MESSENGER and STEREO measurements, Winslow et al (2015) reported this power law equation to be B max ,ejecta = 12.18 +0.75 −0.71 r −1.89±0.14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that our findings (scaling of the peak magnetic field strength in the ejecta with heliocentric distance) are in good agreement with previous statistical studies. In a study published after the initial submission of this manuscript, Good et al (2019) performed a static Lundquist flux rope fitting (Burlaga, 1988;Lepping et al, 1990) for 18 interplanetary flux ropes observed in conjunction between radially aligned spacecraft in the inner heliosphere. Applying the same fitting technique for MESSENGER and STEREO measurements, Winslow et al (2015) reported this power law equation to be B max ,ejecta = 12.18 +0.75 −0.71 r −1.89±0.14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, except for a few studies that used multipoint spacecraft observations (Burlaga et al, 1981;Cane et al, 1997;Farrugia et al, 2011;Good et al, 2015Good et al, , 2018Janvier et al, 2019;Kilpua et al, 2011;Möstl, 2015;Möstl et al, 2009;Prise et al, 2015;Wang et al, 2018;Winslow et al, 2016Winslow et al, , 2018, CME measurements are largely restricted to single-point observations in space (see also discussion in Lugaz et al, 2018). Recently, Good et al (2019) examined the self similarity in the time series profiles of magnetic field structures of 18 interplanetary flux ropes. These lineup events were observed at heliocentric distances ranging from 0.62-9.4 AU, with longitudinal separations between the observing spacecraft being less than 20 • .…”
Section: Introductionmentioning
confidence: 99%
“…If PMS2 is due to flux rope draping, the plane normal and flux rope axis orientation would likely be separated by large acute angles and this is indeed the case, with separations of ∼ 73 • at MESSENGER and ∼ 57 • at STEREO-B. The flux rope orientations used to make this comparison were determined by Good et al (2019).…”
Section: Planar Magnetic Structurementioning
confidence: 99%
“…We also do not consider any CME-CME interaction in the interplanetary space which may change the propagation trajectory of the CME. Assuming that the CMEs expand in a self-similar (Subramanian et al 2014;Good et al 2019;Vršnak et al 2019) way during its interplanetary propagation, we estimate the geometrical parameters of the CME upon its arrival at 1 AU. Using the conservation principle of the magnetic flux and helicity, we determine the magnetic properties of the FR when it is intersected by the spacecraft at 1 AU.…”
Section: Modeling the Interplanetary Flux Ropes Using The Near-sun Obmentioning
confidence: 99%